Medical studies on "choking" in judo, with special reference to electro-encephalographic investigation - Suzuki, K. (Association for the Scientific Studies on Judo, Kodokan, 1958)
Judo, our national sport has become very popular throughout Europe and America, particularly after World War II. Just at the time when judo had begun to be popularized abroad, a problem had arisen in Japan among those interested in judo, i. e. just how dangerous is the "choking" technique ? Hitherto, it was practiced under the populär notion and without scientific basis, that it was a dangerous technique. However, as judo gradually developed into an international sport, it became necessary to decide whether or not to include "choking" among the regulär techniques. As Dr. H. Sato and Mr. M. Morikawa had been conducting scientific investigations on "choking" , the late Prof. Saito made an agreement with the Kodokan authorities to undertake scientific researches on "choking" . The Kodokan authorities had requested to elucidate the following problems. 1. Is there any danger to life ? 2. What is the mechanism which causes unconsciousness ? 3. Does it have any injurious effect on the body ?